Accuracy of early pregnancy diagnosis using interferon-tau (IFN-τ) in Aceh cows - Fisma Amri; Tongku Nizwan Siregar; Gholib Gholib; Husnurrizal Husnurrizal; Juli Melia; Budianto Panjaitan; Teuku Armansyah (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
Interferon-tau (IFN-τ) is a pregnancy signal produced by embryonic trophoblast cells at the time of implantation in a mammal's endometrial wall, which is useful for conveying a message that the mammal can accept the presence of the foreign object (embryo). This study aims to determine the accuracy of early pregnancy diagnosis in Aceh cows by measuring the concentration of IFN-τ. This study involved eight cows aged 3-5 years, weighing 150-250 kg, clinically healthy, and having normal reproduction (have had calves and at least two regular cycles). All cows were estrous-synchronized twice using PGF2ɑ at a dose of 5 ml with 11 days intervals before artificial insemination (AI). Serum collection was performed on days 14, 15, 16, 17, 18 after AI. Based on ultrasound examination, out of eight cows, four (50%) cows were diagnosed as pregnant, and four (50%) cows were diagnosed as not pregnant. Mean (± SD) IFN-τ of pregnant vs. non-pregnant cows on day 14, 15, 16, 17, and 18 were 14.96±8.65 pg/ml vs. 6.14±5.54 pg/mL; 16.74±5.28 pg/mL vs. 4.44±3.51 pg/mL; 14.33±5.9 pg/mL vs. 5.78±5.20 pg/mL; 13.87±5.42 pg/mL vs. 4.38±3.76 pg/mL; and 13.93±6, 16 pg/mL vs. 3.24±2.63 pg/mL, respectively. The lowest IFN-τ concentration in cows that were successfully pregnant was 7.88±1.84 pg/mL. The best timing of IFN-τ for pregnancy diagnosis was on day 15 after AI, with an accuracy of 87.5%, specificity of 100%, and sensitivity of 80%.